TreeEyed: QGIS plugin for tree monitoring - Ruiz-Hurtado, Andres Felipe; Cardoso Arango, Juan Andres (2024)
TreeEyed is a QGIS plugin to leverage AI models for tree monitoring using remote sensing imagery. This plugin seeks to integrate existing and custom AI models for tree monitoring (semantic segmentation, instance segmentation, and object detection) in high resolution RGB imagery.